Determining Prospective Coconut Shell Products using Analytical Hierarchy Process (AHP) - Abidin Abidin (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
Coconut shell can be used as raw material for creative industries, producing ample artistic products. This present work aimed to determine the most prospective product among coconut shell items produced by local craftsman in Pangandaran using AHP. As the result, coco mosaic is found to be the first with priority weight of 0.3339. It has a promising market, for domestic and export product, with price of Rp. 250.000/m2 and US 27 – 40/m2, respectively.